2021
DOI: 10.1186/s13578-021-00706-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-sequencing reveals distinct immune cell subsets and signaling pathways in IgA nephropathy

Abstract: Background IgA nephropathy (IgAN) is the most common primary glomerulonephritis globally. Increasing evidence suggests the importance of host immunity in the development of IgAN, but its dynamics during the early stage of IgAN are still largely unclear. Results Here we successfully resolved the early transcriptomic changes in immune cells of IgAN by conducting single-cell RNA-sequencing (scRNA-seq) with peripheral blood mononuclear cells. The diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…DEGs screening was performed by the "limma" package from R (18). Genes satisfying the conditions of adjusted P value <0.10 and | log2(fold change) |> 0.58 were defined as DEGs between the sensitive group and resistance group (19,20). All DEGs were drawn as heatmaps with the R package "pheatmap".…”
Section: Hub Gene Screening By Degs Screening and Wgcanmentioning
confidence: 99%
“…DEGs screening was performed by the "limma" package from R (18). Genes satisfying the conditions of adjusted P value <0.10 and | log2(fold change) |> 0.58 were defined as DEGs between the sensitive group and resistance group (19,20). All DEGs were drawn as heatmaps with the R package "pheatmap".…”
Section: Hub Gene Screening By Degs Screening and Wgcanmentioning
confidence: 99%
“…In contrast to the findings of previous studies, CD14 and CD16 were not expressed in the peripheral blood monocytes of the testudines, while six marker genes, LGALS1, LY86, PLBD1, MYOF, BPI, and CSF1R, were highly expressed and enriched in response to positive regulation of stimulus and stress, leukocyte chemotaxis, and migration (Supplementary Figure S2A). Previous studies have shown that LGALS1, LY86, PLBD1, BPI, and CSF1R were expressed in monocytes [38][39][40][41][42]. MYOF was observed to be expressed in monocytes for the first time; it was mainly involved in biological processes of response to temperature stimulus and syncytium formation (Supplementary Figure S2B).…”
Section: Discussionmentioning
confidence: 79%
“…The brown module had the highest correlation with IgAN clusters, and 15 hub genes were screened from it according to appropriate thresholds, which were considered to be markers of severe inflammation in IgAN glomeruli. KEGG enrichment analysis indicated that these 15 hub genes were involved in various immune processes such as NK cell–mediated cytotoxicity and cell killing pathways, which are related to the progression and prognosis of IgAN ( 40 ). In addition, hub genes were involved in the complement and coagulation cascades, which play a crucial role in IgAN progression and renal function decline ( 41 ).…”
Section: Discussionmentioning
confidence: 99%